Exploring the Impact of Islamic Javanese Culture on Gender Discrimination in John Michaelson's Annisa - Rahmawati, Amayda Eka; Nurhadi, Muizzu (Sintuwu Maroso Journal of English Teaching, 2023)
This research discusses gender discrimination in the novel Annisa by John Michaelson. The analysis focuses on women's struggle in a male-dominated environment, especially in Islamic Javanese culture. The discussion covered in this analysis includes women's characterization and discrimination that always appears in the novel. The method used in this thesis is a descriptive qualitative method. In addition, this research uses feminist theory. The analysis results show that discrimination obtained by the main character is an unresolved conflict with patriarchal society, especially her family and environment. Annisa rebelled against the existing situation but wanted equal status because she realized that living in an Islamic environment with Javanese culture made her aware of the limited space for movement. Findings suggest that discrimination takes the form of unfair treatment and stereotypes, leading to women's marginalization and subordination to men. The novel shows how Javanese culture plays a role in organizing social norms and influencing character interactions.